Repotenciación del marcador de juegos de una Unidad Educativa mediante IOT. - Tapia Vega, Fausto Saúl (2023)
The present technological proposal contemplates the repowering of the electronic scoreboard of the "Victoria Vásconez Cuvi" Educational Unit, the design is based on the control through the Internet of Things (IoT), and the selection of electronic devices, such as the Arduino Mega and the NodeMCU ESP8266, in order to provide a solution to the deficiencies of its operation, since its current operation is done through a keyboard, which is not fully operational and therefore its connection presents intermittencies. The design of the proposal to upgrade the electronic scoreboard is necessary because the current model shows several limitations, also presents failures in its main connections, making the system obsolete, therefore, the technological solution is developed through software and the programming of the electronic elements that provide the facilities to achieve better communication, control and data visualization. During the development, schematic diagrams have also been made to help in the operation and maintenance of the system, including the design of PCB boards and connection diagrams. Once the technological proposal is completed, a fully operational system is obtained, controlled by IoT, which together with the design of programming algorithms and electronic devices allows the management of the scoreboard through the Telegram application, providing a better connection and solving the problem of intermittency, in addition the end user has an easy to use interface. The system has been verified through various functional tests, verifying that it meets the requirements for remote operation and resolving the connection problems. Once the tests were completed, the electronic scoreboard was installed and the end users were given an induction on its use.